There is more to the picture than meets the eye: adaptation for crypsis blurs phylogeographical structure in a lizard. (7th July 2016) - Díaz, José A.; Verdú‐Ricoy, Joaquín; Iraeta, Pablo; Llanos‐Garrido, Alejandro; Pérez‐Rodríguez, Antón; Salvador, Alfredo
Abstract: Aim: We examined dorsal coloration in and genetic relationships among Iberian populations of the lizard Psammodromus algirus to determine the extent to which the current distribution of phenotypic variation is correlated with phylogeographical history or local environmental conditions. Location: Iberian Peninsula, western Palaearctic. Methods: We sequenced mitochondrial DNA (ND4 and adjacent tRNAs genes) in 36 populations, and seven microsatellite loci in eight representative populations. In 23 populations, lizards were classified according to the presence and intensity of a dorsal striped pattern, the heritability of which was estimated by means of mother–offspring regressions. To determine whether colour pattern is an adaptation for crypsis, we compared the time taken by humans to detect striped and unstriped lizards in different environments. Results: The analysis of mtDNA revealed an ancient split between a western clade, subdivided into south‐ and north‐western haplogroups, and an eastern clade with central, south‐eastern and eastern haplogroups. In contrast, nuclear markers showed a post‐glacial admixture of central and western haplogroups, with the central haplogroup apparently isolated from the rest of its clade. This was consistent with variation in the dorsal striped pattern, a heritable phenotypic trait: central and western lizards were unstriped, whereas eastern lizards were striped. We then suggest that dorsal coloration promotes crypsis: in eastern locations detection times were longer for striped than for unstriped lizards, whereas the opposite was true in western and central locations. Main conclusions: Our results indicate that natural selection for crypsis may promote not only divergence within clades, as suggested by the apparent isolation between unstriped central lizards and striped members of eastern haplogroups, but also admixture between them. We conclude that ecologically driven selection is crucial for understanding the phylogeographical background of phenotypic variation, because recent adaptation to the environment can blur the effects of ancestral isolation.